Detection of aflatoxins in aonla fruits and their products - and C. UMA MAHESWARI3, P. NALLATHAMBI1*, A. NAGARAJA2 (Indian Phytopathology, 2010)
Post harvest rots affect the market value of aonla fruits. Recurrent sampling from the Bikaner (Rajasthan) fruitmarket area depicted a variable intensity of fungal rots on aonla fruits. Aspergillus rots were commonly observed on thecommercial varieties NA-6, NA-7 and Krishna. The maximum incidence (23.2 %) was observed in cv. Krishna followed by 17.8 %Â in NA-6 and 10 % in NA-7. Out of 21 isolates of Aspergillus species, 4 isolates of A. flavus were proved to be pathogenic to cv.Â NA-6 and NA-7. In another experiment, aonla fruits kept in polythene bags up to 30d by normal method of packing (sealing)showed 52% incidence by A. niger. However, its association was less in aonla products i.e. candy (5 %) and shreds (10%).Toxigenic nature of A. flavus isolates was confirmed by detecting the aflatoxins through thin layer chromatogram (TLC). Allisolates of A. flavus expressed prominent spot of aflatoxin B2 but were observed to be negative to produce aflatoxin B1 and G2.Â A. flavus isolates (Af-1, Af-3 and Af-4) inoculated on fruits (cv. NA-6) produced B2 and none of other compounds were detectedÂ from colonized tissues. Additionally, yellow fluorescence compounds (Rf 0.52, 0.58 and 0.64) which are unknown compoundsÂ were detected only from the pathogen grown on culture medium. The possible reasons for variation in aflatoxin production inÂ culture medium and aonla fruits are discussed in this paper.